Nanoparticle and nanosphere mask for etching of ITO nanostructures and their reflection properties. Issue 1 (23rd September 2014) - Xu, Cigang; Deng, Ligang; Holder, Adam; Bailey, Louise R.; Leendertz, Caspar; Bergmann, Joachim; Proudfoot, Gary; Thomas, Owain; Gunn, Robert; Cooke, Mike
<x xml:space="preserve">Abstract</x> Au nanoparticles and polystyrene nanospheres were used as mask for plasma etching of indium tin oxide (ITO) layer. By reactive ion etching (RIE) processes, the morphology of polystyrene nanospheres can be tuned through chemical or physical etching, and Au nanoparticle mask can result in ITO nanostructures with larger aspect ratio than nanosphere mask. During inductively coupled plasma (ICP) processes, Au nanoparticle mask was not affected by the thermal effect of plasma, whereas temperature of the substrate was essential to protect nanospheres from the damaging effect of plasma. Physical bombardment in the plasma can also modify the nanospheres. It was observed that under the same process conditions, the ratio of CH4 and H2 in the process gas can affect the etching rate of ITO without completely etching the nanospheres. The morphology of ITO nanostructures also depends on process conditions. The resulting ITO nanostructures show lower reflection in a spectral range of 400–1000 nm than c‐Si and conventional antireflection layer of SiNx film. <inline-graphic xlink:href="ark:/27927/pgh3730r9ck" content-type="pssa201431228-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> ITO nanostructures obtained after etching (scale bar = 200 nm).